A good night for ghosts - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series. Merlin missions, 2017)
Jack and Annie must travel back in time to New Orleans in 1915 to help a teenaged Louis Armstrong fulfill his destiny and become the "King of Jazz."